Application of methodological strategies based on music for listening skill development to students of primer año de bachillerato at colegio San Vicente de Paúl, in the city of Riobamba, Chimborazo province, during 2014-2015 academic year - Ureña Lara, David Antonio (2016)
This research work had as main purpose to investigate whether the application of methodological strategies based on music could develop listening skills in students of Primer año de bachillerato in “San Vicente de Paul” high school, in Riobamba city. In order to overcome the failure to have such students to hear the foreign language, to perceive and understand the new vocabulary which is indispensable to communicate successfully with others. For conducting successfully this research, new and classic methodological strategies based on music were applied, such as “Fill in the Blanks”, “Line Ordering” and “Mixed Songs”, which stimulated students to feel relaxed and active in class. The population was composed of 75 students of Primer año de bachillerato in “San Vicente de Paul” high school, and the type of applied research was used, which allowed us to implement the aforementioned methods in a systematic and organized way to get the results. A test and observation guide as data collection tools were used. At the conclusion of the research, the presentation and discussion of statistical results, a significant change was determined because the students improved their sense of hearing significantly their listening skill in English. In addition, they began to be more interested in learning the foreign language through songs, their motivation level was increased, so relaxed they felt while learning new vocabulary. For these reasons, as conclusion, it is recommended to teachers and students the use of songs to increase the listening skills, to become familiar with grammar, pronunciation, idioms, and dialects, which increase the sense of hearing and understanding, which enables them to communicate better